Upaya Guru Pendidikan Agama Islam Dalam Menanamkan Nilai-Nilai Moderasi Beragama di SMAN 14 Surabaya - Saputra, Abdul Azis Eka; M, Mufaizah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Religious moderation is very important to be instilled in students in order to create an environment that is peaceful, comfortable and safe from various threats. This study aims to determine the efforts of Islamic Religious Education teachers in instilling religious moderation values, to find out the supporting factors and strategies of PAI teachers in instilling religious moderation values, to find out the supporting and inhibiting factors of PAI teachers' efforts in instilling religious moderation values at SMAN 14 Surabaya. The type of this research is field research (Field Research) which is descriptive qualitative, the informants of this research include principals, PAI teachers, and students, data collection techniques using interviews, documentation and observation. data analysis techniques are inductive based on the data obtained, then developed or described qualitatively. Religious moderation is very important to be instilled in students in order to create an environment that is peaceful, comfortable and safe from various threats. This study aims to determine the efforts of Islamic Religious Education teachers in instilling religious moderation values, to find out the supporting factors and strategies of PAI teachers in instilling religious moderation values, to find out the supporting and inhibiting factors of PAI teachers' efforts in instilling religious moderation values at SMAN 14 Surabaya. Based on the results of the study, it can be concluded that the efforts of PAI teachers in instilling the value of religious moderation at SMAN 14 Surabaya by delivering material on tolerance and respect for diversity, giving advice during learning both at the beginning, middle and at the end, exemplary PAI teachers in accordance with the duties of teachers as role models for their students, accustoming students to follow religious activities held at school. Supporting factors are infrastructure in the form of a mosque that supports the implementation of religious activities, as well as support from the school and parents, inhibiting factors are the lack of student attention in paying attention to lectures, advice given by the teacher.